2023
DOI: 10.3390/antibiotics12050889
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Anti-Toxoplasma gondii Efficacy, Cytotoxicity, and GC/MS Profile of Pleopeltis crassinervata Active Subfractions

Abstract: Pleopeltis crassinervata (Pc) is a fern that, according to ethnobotanical records, is used in Mexican traditional medicine to treat gastrointestinal ailments. Recent reports indicate that the hexane fraction (Hf) obtained from Pc methanolic frond extract affects Toxoplasma gondii tachyzoite viability in vitro; therefore, in the present study, the activity of different Pc hexane subfractions (Hsf) obtained by chromatographic methods was evaluated in the same biological model. Gas chromatography/mass spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…These results agree with the ethnobotanical record of P. crassinervata which reported that the frond harbors curative properties [6]. For these reasons we decided to perform the fractionation of FMeOHe according to the methodology established in our previous research, with the aim of elucidating its antibacterial activity [20]. After FMeOHe partition, a second antibacterial assay was performed wherein FMeOHe and its three fractions were evaluated.…”
Section: Antibacterial Assaysupporting
confidence: 80%
See 4 more Smart Citations
“…These results agree with the ethnobotanical record of P. crassinervata which reported that the frond harbors curative properties [6]. For these reasons we decided to perform the fractionation of FMeOHe according to the methodology established in our previous research, with the aim of elucidating its antibacterial activity [20]. After FMeOHe partition, a second antibacterial assay was performed wherein FMeOHe and its three fractions were evaluated.…”
Section: Antibacterial Assaysupporting
confidence: 80%
“…Additionally, an investigation revealed that Hf from P. crassinervata exerted an effect on T. gondii tachyzoites with an IC 50 value as low as 16.9 µg/mL. This finding is particularly noteworthy given the taxonomic similarities between T. vaginalis and T. gondii, as both protozoan parasites are affected by the same fractions [19,20]. This study showed that Hsf6 with trichomonacidal activity is primarily composed of terpenes.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations